Regulation of clock and clock-controlled genes during morphine reward and reinforcement: Involvement of the period 2 circadian clock. (July 2022) - Custodio, Raly James Perez; Kim, Mikyung; Sayson, Leandro Val; Ortiz, Darlene Mae; Buctot, Danilo; Lee, Hyun Jun; Cheong, Jae Hoon; Kim, Hee Jin
Background: Morphine abuse is a devastating disorder that affects millions of people worldwide, and literature evidence indicates a relationship between opioid abuse and the circadian clock. Aim: We explored morphine reward and reinforcement using mouse models with Per2 gene modifications (knockout (KO); overexpression (OE)). Methods: Mice were exposed to various behavioral, electroencephalographic, pharmacological, and molecular tests to assess the effects of morphine and identify the underlying mechanisms with a focus on reward and reinforcement and the corresponding involvement of circadian and clock-controlled gene regulation. Results: Per2 deletion enhances morphine-induced analgesia, locomotor sensitization, conditioned place preference (CPP), and self-administration (SA) in mice, whereas its overexpression attenuated these effects. In addition, reduced withdrawal was observed in Per2 KO mice, whereas an augmented withdrawal response was observed in Per2 OE mice. Moreover, naloxone and SCH 23390 blocked morphine CPP in Per2 KO and wild-type (WT) mice. The rewarding (CPP) and reinforcing effects (SA) observed in morphine-conditioned and morphine self-administered Per2 KO and WT mice were accompanied by activated μ-opioid and dopamine D1 receptors and TH in the mesolimbic (VTA/NAcc) system. Furthermore, genetic modifications of Per2 in mice innately altered some clock genes in response to morphine. Conclusion: These findings improve our understanding of the role of Per2 in morphine-induced psychoactive effects. Our data and those obtained in previous studies indicate that targeting Per2 may have applicability in the treatment of substance abuse.